CreativeLab_Sci&Math: open educational resources in teacher education - Linhares, Elisabete (2020)
To face the important challenges of today’s demanding and competitive digital society, multidisciplinary knowledge, new skills and competences are needed. These challenges necessarily imply the change of teaching practices and a strong commitment and support of teacher education throughout the innovation process. The CreativeLab_Sci&Math project was developed by teacher educators of the Department of Mathematic and Natural Sciences of the School of Education/Polytechnic Institute of Santarém and consists of involving future teachers in an innovative learning environment with a focus on integration of mathematics and science. In this project, inquiry and project-based learning interdisciplinary activities are carried out using digital technologies, which includes programming and robotics activities. The main goals of this project are to prepare teachers and future teachers to support innovation initiatives in schools, concerning mathematics and science. One way to achieve these goals involves producing Open Educational Resources and making them available on several online platforms, such as Casa das Ciências® and ERTE (Portuguese Ministry of Education). The produced resources have received national awards and resulted from the work developed by these educators in coteaching, their participation in European projects and their experience in mobility programs.